Influence of the use of dental prostheses in balance and body posture. - Shiraishi, Cristian Fernando; Salgado, Afonso Shiguemi Inoue; Kerppers, Ivo Ilvan; Furmann, Meiriélly; Oliveira, Thais Barbosa de; Ribeiro, Larissa Gulogurski; Pires, Juliana Aparecida Wosch; Rolão, Marcos Paulo Polowei; Eltchechem, Camila da Luz; Suckow, Patricia Tyski (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: The concept of body posture involves balance, neuromuscular coordination and adaptation. Automatic postural responses are adjusted to meet the needs of interaction between systems of postural organization and the environment. Postural control is to maintain body position seeking stability and orientation in space, and the maintenance of posture and balance is directly related to three main systems: visual, vestibular and proprioceptive, whose junction ensures body balance. Other factors may be related to this control, such as the use of prostheses, among them the dentures that provide the balance of the mouth and jaws, through neuromuscular balance, helping to balance the body as a whole. Stabilometry assesses postural balance through the quantification of postural sway in the orthostatic position on a force platform. Objective: To evaluate the influence of the use of dental prostheses in maintaining balance and posture through baropodometry. Method: The study included 10 women with an average age of 65 years old, all using dental prosthesis, which remained on the platform for 30 seconds, with the prosthesis, repeating the procedure without the use of the prosthesis. Results: As the postural balance is given by the sum of the balance of all body structures, where all must be wholesome, and may include dental arch, in this case replaced by dental prosthesis, there was a direct contribution of using it over body balance as a whole, since there was a decrease in the number of oscillations of the body centroid and radial displacement, among individuals who use dental prosthesis. Conclusion: The present study demonstrated that there is a direct influence of the use of dental prostheses on posture and body balance.